Modification of the rotating model method for studying the sexual discriminative abilities of butterflies (Lepidoptera) - Tsuyoshi TAKEUCHI (European Journal of Entomology, 2015)
Recently, Imafuku & Kitamura (Eur. J. Entomol. 112, 2015: 328-333) succeeded in inducing males of two territorial butterflies, Chrysozephyrus smaragdinus and Neozephyrus japonicus, to respond to wing models by rotating the models. Based on the results of two-choice tests in which males stayed longer within 50 mm of the female model than the male model the authors claim that males of both of these butterflies identify females using the patterns on the wings. I think this study provides a new method for studying the discriminative abilities of butterflies. In contrast to static models, however, butterflies attracted to rotating models do not land on the models but remain at some distance from the moving models. A close approach to a model, therefore, does not always reflect the animal's preference. I suggest a better way of using this method for testing the discriminative ability of butterflies.